Interference of coronal enamel and dentin thickness and ambient light on pulse oximetry interpretation - Julio Almeida SILVA; Ana Helena Gonçalves de ALENCAR; Larissa Emanuelle SESTARI; Higor Almeida BARBOSA; Patrícia Correia de SIQUEIRA; Daniel Almeida DECURCIO; Fernando Branco BARLETTA; Carlos ESTRELA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study evaluated the interference of enamel and coronal dentin thickness and ambient light in pulse oximetry interpretation, using SaO2the human finger as a reference. Forty-two intact human permanent mandibular molars were sectioned mesiodistally in the central portion. Buccal and lingual dentin surfaces were drilled, and 4 mm, 3 mm and 2 mm enamel/dentin thicknesses were interposed between finger and device, after which SaO2 levels were measured by finger pulse oximetry. A reference device was designed to align pulse oximeter light-emitting diode, buccal surface of tooth, little finger, lingual surface of tooth and photodiode. Variables were described as means and standard deviation, and the confidence interval was reported. Repeated measures analysis of variance (ANOVA) was used to compare the groups, followed by Bonferroni correction. Student t test for paired samples was used to determine presence of ambient light (α = 0.05). Mean SaO2 level was lower at 4.0 ± 0.2 mm thickness, regardless of presence or absence of ambient light (92.7% and 89.3%). The other thicknesses yielded values of 95.5% and 94.5% at 3.0 ± 0.2 mm, and 96.4% and 96.0% at 2.0 ± 0.2 mm (p < 0.001). There were significant differences between SaO2 values at 4.0 ± 0.2 mm, 3.0 ± 0.2 mm and 2.0 ± 0.2 mm thicknesses, in the presence of ambient light. Mean SaO2 level in positive control was 96.3%, and mean pulse rate was 69.5 bpm in presence of ambient light; in the absence of light, these values were 96% and 70.5 bpm. Enamel and dentin thickness interfere with SaO2, regardless of presence or absence of ambient light. The lowest SaO2 levels were found for the thickest tooth samples.